BEYOND RACE: A QUANTITATIVE STUDY OF THE DISCIPLINE GAP AMONG PREDOMINANTLY BLACK HIGH SCHOOLS IN CHICAGO - Agudelo Acevedo, Felipe Ignacio (2016)
Exclusionary discipline in schools has been proven to develop negative consequences in the life of students who are exposed to this kind of punishment in schools. Research in this area has shown that Out of School Suspensions (OSS) more frequently affect Black male students. During this research I argue that OSS are not necessarily caused by the race of the student but by some other factors that make some predominantly Black high schools more likely to use OSS than others. A question to be answered in the area of school discipline is related to what contributes to the odds that schools with similar demographics do not have similar out of school suspension rates. The present research asked about the risks that could predict the odds that a predominantly Black high school may have an out of school suspension rate higher or lower than the state of Illinois or higher than the average within the sample. It basically focuses on the discipline gap among predominantly Black high schools in Chicago. For the purpose of this research race was not considered as a variable, it was only used as an inclusion factor of the sample. This research was conducted from a social ecological model with a population of 30 predominantly Black high schools in Chicago. It investigated the contribution of three groups of independent variables in predicting out of school suspension rates. For the purpose of this research, a quantitative approach was developed using Chi-square and logistic regression methods for data analysis. This research found that the variable called percentage of students with disabilities was found to be statistically significant when predicting the odds that a school will suspend above the average out of school suspension rate within the sample. This research contributed to the understanding of a new approach of out of school suspensions within predominantly Black high schools and the importance of schools in the disciplinary actions considered for students with disabilities